Perbandingan Pendapatan Dan Pengeluaran Rumah Tangga Petani Padi Sawah Di Desa Tolok Kecamatan Tompaso - Giroth, Indah Riva; Waney, Nordy F.L.; Katiandagho, Theodora Maulina (AGRI-SOSIOEKONOMI, 2023)
The aim of this study was to compare the income and expenses of farming households in Tolok Village, Tompaso District in one growing season. The research was conducted for 3 months, from January to March 2022. The data analysis method used in the research was descriptive statistical analysis, namely by calculating the average income and tabulating the data to find out income, income of paddy rice farmers and expenditure on food and non-food consumption. The data used are primary data and secondary data. Primary data were obtained through direct interviews with farmers who were research respondents using a list of questions that had been prepared. Secondary data was obtained from related institutions, namely the village office, the internet via Google Search and Google Books, articles and scientific journals. The results of the study show that farm households still depend on income from farming. The average income earned by respondent rice farming households in Tolok Village is greater than that spent by farmers for their household needs. The total income received is IDR511,115,000 so that the total income per year is IDR1,022,230,000 and the total expenditure for farming households is IDR105,480,000 each year. The income of lowland rice farmers is sufficient to meet the needs of lowland rice farmers and their families. This also provides opportunities for the respondent farmer households to save money, open a business or send their children to school.